Perceptions of students and teachers about the motivational climate in university classes mediated by technology - Chiarino, Nicolás (2024)
Introduction: The Classroom Motivational Climate (CMC) studies how teaching action patterns are related to student motivation. Objective: To investigate student and teacher perceptions of CMC in first-year university classes mediated by technology and analyze possible differences according to the teacher-student ratio. Method: A qualitative methodology was used through a case study design, where 144 students and 18 teachers participated. The instruments used were pedagogical narratives and semi- structured interviews. A content analysis was carried out with a deductive approach. The reliability of the inter-coding process was verified by Krippendorff’s alpha coefficient (α=.84). Results: The most relevant components of CMC according to students and teachers were: affection and emotional support, encouragement of participation, clarity in the organization, use of novelty, frequent use of examples and promotion of autonomy. Differences were evident between student and teacher perceptions, and between classes with different teacher-student ratios. Discussion and conclusions: The results of this study can contribute to the development of teacher training programs and institutional actions aimed at promoting motivation for learning in university teaching mediated by technology.